Ring opening of donor-acceptor-type cyclopropene unveils electrophilic ketene with vinylogous [4 C + n] periselective cyclization mode - Jianhong Huang; Jiahang Li; Shenli Liu; Wanyao Zhao; Yan Xia; Xiaoyan Liu; Kuizhan Shao; Wenliang Li; Haiyan Yuan; Jinbo Zhao (Nature Communications)
Abstract Since its advent 120 years ago, the [2+n] coupling cyclization of ketene has been prevalently used for the synthesis of N- and O-heterocycles. In contrast, its vinylogous version, i.e., use of alkenyl ketene as 4 C synthon, remain elusive. We report herein that in the rare SN1-type ring-opening of electron-deficient cyclopropene, the initially formed sp2-carbocation-containing zwitterionic intermediate undergoes facile 1,4-alkoxy migration to generate a functionalized alkenyl ketene. This electrophilic intermediate not only allows for challenging N-nucleophiles to be engaged in the conventional ketene [2+n] reactions (n = 1 ~ 3), also unveiled the vinylogous [4+n] cyclization mode, as exemplified by the [4 + 1] and formal [4 + 4] cyclization to construct pyrrolidinone and azocine frameworks. The protocol offers a unified entry to a distinct class of lactam scaffolds that exhibit anti-cancer potential, constituent key natural product scaffold and display interesting 1e- and 2e- reactivities. This work reveals a broader synthetic potential of the facile SN1 type ring-opening of cyclopropene as “dehydro”-donor-acceptor cyclopropane (DDAC) substrate, and could have ramifications in ketene chemistry, N-heterocyclic chemistry and related medicinal research, as well as the donor-acceptor system chemistry.